Does cholecystectomy affect the sphincter of oddi and the ampulla of vater? Ali holecistektomija vpliva na oddijev sfinkter in ampulo papile vateri? - Skalicky, Marjan (Acta Medico-Biotechnica, 2021)
Purpose: About 20-50% of cholecystectomized patients complain of dyspeptic problems after gallstone surgery. I hypothesized that some of these problems do not arise from primary gallbladder disease, but are due to problems of duodenal origin.Methods: I examined 80 patients using endoscopic ultrasound (EUS) before gallstone surgery (AOP). I repeated the examination 3 months (POP3) and 6 months (POP6) after the surgery. Fifty patients who underwent surgery were symptomatic; 30 were asymptomatic. In all patients, an analysis of the papilla of Vater (PV) was carried out with a special focus on the visibility of the sphincter of Oddi complex (SOC) and the ampulla of papilla (AP).Results: The visibility of the SOC was significant in the measurements AOP/POP3 (p
Keywords: papilla of Vater; sphincter of Oddi; cholecystectomy; endoscopic ultrasound